MANAJEMEN PENGELOLAAN TEKNOLOGI DALAM KONTEKS MEDIA PEMBELAJARAN PAI - Fajar Ardian; Weriana Weriana; Handoyo Saputra; Andri Suryana; Arifen Anggara; Ami Latifah (CV. ADIBA AISHA AMIRA, 2023)
This research aims to analyze the use of learning media technology in Islamic Religious Education learning. This research method is a type of qualitative research using library research and field studies. The method used in this research is qualitative through observation, interviews and documentation. The results of this research show that Islamic Religious Education Teachers in Elementary Schools in learning planning have created a syllabus and prepared lesson plans before carrying out teaching and learning activities to serve as a guide in the learning process. In the core of the lesson, technology lesson media is used through PPT and learning videos. Learning management has a crucial role in learning activities. Effective learning media management will achieve Islamic Religious Education learning objectives efficiently and effectively.